Error-correcting Coding Usage for Data Transmission Through Power Lines - Aleksey Ishchenko; Vladimir Shevelev; Alexander Naronov; Alexander Tcherepanov; Boris Shulgin (Institute of Advanced Engineering and Science, 2018)
A concept of data transmission within downhole telemetry systems in oilfield industry through power lines is presented. Based on this concept, MATLAB/Simulink models simulating communication lines in downhole telemetry systems are built, which can be used as prototypes for development of real systems. The most appropriate signal modulation methods for data transmission in downhole telemetry systems are suggested and discussed. The influence of high-voltage interference on signal transmission through power line from downhole unit to ground based unit is simulated. Usage of error-correcting coding methods for data transmission such as Hamming code, Reed-Solomon code, BCH code is suggested, and its efficiency is demonstrated.